A solid electrolyte and its preparation method and application

By using solid electrolytes prepared by natural inorganic mineral kaolin, the low performance problem caused by aqueous zinc ion batteries is solved due to aqueous electrolytes, uniform deposition of zinc ions and stability of the positive electrode material are achieved, and the cycle stability and life of the battery are improved.

CN118610610BActive Publication Date: 2025-05-09HAINAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410858567.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-05-09
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The aqueous zinc ion battery causes zinc metal negative dendrites, hydrogen evolution, corrosion and dissolution of positive electrode materials due to aqueous electrolytes, resulting in low battery performance.

Method used

A solid electrolyte prepared from natural inorganic mineral kaolin or sepiolite powder is used. The electrolyte has the ability to conduct zinc ions, can guide the uniform deposition of zinc ions, and inhibit the dissolution of the positive electrode material.

Benefits of technology

It effectively solves the dendrites and corrosion problems of zinc metal negative electrodes, inhibits the dissolution of vanadium-based positive electrodes, and improves the long cycle stability, rate performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118610610B_ABST
    Figure CN118610610B_ABST
Patent Text Reader

Abstract

The embodiments of the present application relate to a solid electrolyte and its preparation method and application, which belongs to the technical field of aqueous zinc ion batteries. The embodiments of the present application aim to solve the technical problem that the practical application of existing zinc ion batteries is affected by zinc metal negative electrode dendrites, hydrogen evolution, corrosion and dissolution of positive electrode materials caused by aqueous electrolytes, resulting in low battery performance. A method for preparing a solid electrolyte in the embodiments of the present application comprises the following steps: mixing natural inorganic minerals after centrifugal cleaning of impurities with zinc salt electrolytes for ion exchange, and obtaining a solid electrolyte after drying. The solid electrolyte provided in the embodiments of the present application has the ability to conduct zinc ions, can allow reversible shuttling of zinc ions and guide the uniform deposition of zinc ions, and can inhibit the dissolution of positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of aqueous zinc ion batteries, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] Aqueous zinc-ion batteries are an electrochemical energy storage device that is booming due to their environmental protection, safety, low cost, and large capacity. However, the practical application of aqueous zinc-ion batteries is hampered by problems such as zinc metal negative electrode dendrites, hydrogen evolution, corrosion, and dissolution of positive electrode materials caused by aqueous electrolytes, resulting in low battery performance. Reducing active water molecules is the key to solving the problems of positive and negative electrodes. At present, the existing aqueous electrolytes are usually treated by electrolyte additives or by establishing positive and negative electrode SEI protective layers to inhibit the erosion of active water, but the problem of active water erosion on the positive and negative electrodes cannot be truly solved. Therefore, the development of new solid electrolytes with excellent zinc ion conductivity is an effective way to achieve dendrite-free zinc negative electrodes and inhibit the dissolution of positive electrode materials. In addition, the severe dissolution of vanadium in vanadium-based positive electrodes during low current density cycling often leads to the destruction of the lattice structure and a decrease in capacity retention, which limits the practical application of vanadium-based positive electrodes. Reducing the content of free water molecules in the electrolyte and avoiding direct contact between free water molecules and vanadium-based positive electrodes are effective ways to inhibit vanadium-based dissolution. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a solid electrolyte and a preparation method and application thereof. The solid electrolyte has the ability to conduct zinc ions, can allow reversible shuttling of zinc ions and guide the uniform deposition of zinc ions, and can inhibit the dissolution of positive electrode materials. It can effectively solve the problems of low battery performance caused by zinc metal negative electrode dendrites, hydrogen evolution, corrosion and dissolution of positive electrode materials caused by aqueous electrolytes in the practical application of existing zinc ion batteries.

[0004] A first aspect of an embodiment of the present application provides a method for preparing a solid electrolyte, comprising the following steps:

[0005] The natural inorganic minerals after centrifugal cleaning of impurities are mixed with zinc salt electrolyte for ion exchange, and solid electrolytes are obtained after centrifugal cleaning and drying.

[0006] This embodiment uses widely used natural inorganic mineral kaolin or sepiolite powder as raw materials to prepare a solid electrolyte with the inherent properties of an electronic insulator and a zinc ion conductor. Thanks to the two-dimensional layered structure, anhydrous state and intrinsic zinc ion conductor of the solid electrolyte, it not only effectively provides a convenient zinc ion transmission pathway, guides the uniform deposition of zinc ions, and reduces the side reactions at the negative electrode / electrolyte interface, but also effectively inhibits the dissolution of vanadium, stabilizes the vanadium-based crystal structure, and ensures the reversible insertion behavior of zinc ions at the positive electrode / electrolyte interface, so that the battery has the advantages of high stability, high rate performance and long cycle life.

[0007] In some embodiments that may include the above embodiments, the following steps are specifically included:.

[0008] (1) washing kaolin / sepiolite powder with deionized water by centrifugation and drying to obtain impurity-free powder for later use;

[0009] (2) The impurity-free powder is mixed with a zinc salt electrolyte, and the mixture is fully stirred to obtain a mixture, and the mixture is centrifuged, washed, and dried to obtain a solid electrolyte.

[0010] In some embodiments that may include the above embodiments, step (2) specifically includes the following process:

[0011] The impurity-free powder and zinc salt electrolyte are placed in a beaker, a stirring magnet is added, and the mixture is fully stirred at 400-600 r / min for 2-14 hours to obtain a mixture, and then the mixture is centrifugally washed with deionized water and dried to obtain a solid electrolyte.

[0012] In some embodiments that may include the above embodiments, the impurity-free powder and the zinc salt electrolyte are used in a ratio of (1g-5g): (15ml-75ml); or

[0013] The usage ratio of the impurity-free powder and the zinc salt electrolyte is (2g-4g):(25ml-50ml).

[0014] In some embodiments that may include the above embodiments, the zinc salt electrolyte is at least one of zinc sulfate electrolyte, zinc trifluoromethanesulfonate electrolyte, zinc chloride electrolyte, and zinc acetate electrolyte; preferably, the zinc salt electrolyte is zinc sulfate electrolyte; or

[0015] The concentration of the zinc salt electrolyte is 1.5-3 mol / L.

[0016] In some embodiments that may include the above embodiments, the following steps are also included:

[0017] (3) Weigh the solid electrolyte and use a tablet press to make a stable sheet-like solid electrolyte.

[0018] Preferably, step (3) is specifically as follows: weighing 0.1-0.2 g of solid electrolyte, and using a tablet press to tablet, so as to obtain a stable sheet-like solid electrolyte, wherein the thickness of the solid electrolyte is 1 mm-8 mm; preferably 2 mm-6 mm; or

[0019] In some embodiments that may include the above embodiments, the tableting pressure of the tablet press is 800-1200 Pa; preferably 900-1000 Pa.

[0020] In a second aspect, the embodiments of the present application also provide a solid electrolyte prepared by the above-mentioned preparation method.

[0021] The third aspect of the embodiments of the present application also provides the use of the above-mentioned solid electrolyte in the preparation of aqueous zinc-ion batteries and aqueous zinc-iodine batteries.

[0022] The fourth aspect of the embodiment of the present application further provides an aqueous zinc ion battery, the aqueous zinc ion battery comprising a battery housing and a positive electrode, a diaphragm and a negative electrode located in the battery housing, wherein the diaphragm is the above-mentioned solid electrolyte; or

[0023] The positive electrode is at least one of a vanadium-based material, a manganese-based material and iodine-fixing high-activity carbon.

[0024] Preferably, the vanadium-based material is NVO; the manganese-based material is MnO2; and the iodine-fixing high-activity carbon is UPC@I2.

[0025] It should be noted that the solid electrolyte plays the dual role of separator and electrolyte, which further saves costs.

[0026] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0027] 1. The electrolyte in the embodiment of the present application is composed of low-cost natural mineral kaolin. Kaolin and its unique two-dimensional layered structure are used to guide uniform zinc deposition, so that it has excellent zinc ion conductivity, which can solve the dendrite and corrosion problems of zinc metal negative electrode. Kaolin solid electrolyte contains almost no water molecules, and can inhibit the dissolution of vanadium-based positive electrode under low current, solving the problem of vanadium-based positive electrode dissolution. Thereby improving the long cycle stability of the battery, so that the battery has the advantages of high stability, high rate performance and long cycle life. In addition, the solid electrolyte of the present application can also inhibit the dissolution of manganese positive electrode.

[0028] 2. The preparation process of the present application is simple, with good repeatability, and can be prepared on a large scale and mass-produced; kaolin is selected as the solid electrolyte, which has a simple production process, abundant resources, low cost, excellent performance, and can be used in aqueous zinc-ion batteries and zinc-iodine batteries over a large area, and has broad applicability to battery systems; the embodiments of the present application provide a reference for the design of natural mineral-based solid electrolytes, pave the way for the large-scale preparation and application of solid electrolytes in water-based secondary batteries, and have broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 The SEM, EDS and optical photographs of the solid electrolyte prepared in Example 1;

[0031] Figure 2 The Zn / / Zn symmetric cells prepared in Example 1 and Comparative Example 1 were -2 -0.1mA·cm -2 Long cycle stability diagram of ;

[0032] Figure 3 This is a scanning electron microscope (SEM) comparison of the Zn / / Zn symmetric battery obtained in Example 1 and Comparative Example 1 after 10 cycles;

[0033] Figure 4 Zn / / NH4V4O prepared in Example 1 and Comparative Example 1 10 Full battery at 500mA·g -1 Comparison of cycling performance under current density;

[0034] Figure 5 Zn / / NH4V4O prepared in Example 1 10 Full cell rate performance diagram;

[0035] Figure 6 The Zn / / MnO2 full battery prepared in Example 1 and Comparative Example 1 was subjected to 500 mA·g -1 Comparison of cycling performance under current density;

[0036] Figure 7 The Zn / / UPC@I full cell prepared in Example 1 was subjected to 1000 mA·g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0038] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0039] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0040] Example 1

[0041] The method for preparing the solid electrolyte of this embodiment comprises the following steps:

[0042] First, take 5g of kaolin, wash it with deionized water by centrifugation, and dry it to obtain a powder without impurities for later use;

[0043] 2g of kaolin and 25ml of 2mol / L zinc sulfate electrolyte were weighed in a beaker, and a stirring magnet was added. The mixture was stirred for 2-12h at a speed of 500r / min. After the stirring was completed, a mixture was obtained. The mixture was washed by centrifugation with deionized water and dried to obtain a solid electrolyte powder. 0.15g of the solid electrolyte powder was weighed and tableted by a tablet press at a tableting pressure of 1000Pa to obtain a solid electrolyte. The solid electrolyte was marked as KL-Zn.

[0044] The solid electrolyte prepared in this embodiment is used to form a button-type zinc ion symmetrical battery with zinc sheets and zinc sheets (the zinc sheets are cut into pieces, the positive and negative electrodes are both zinc sheets, the intermediate electrolyte is KL-Zn, and the positive electrode grams, negative electrode grams, gaskets, springs, and battery casings form a Zn / / Zn symmetrical battery).

[0045] The solid electrolyte prepared in this example is used to assemble a button-type zinc ion full battery and a zinc iodine battery with a zinc sheet as the negative electrode and a positive electrode sheet (a zinc sheet is cut into pieces as the negative electrode, and NH4V4O is weighed). 10 , MnO2, UPC@I active material, binder polyvinylidene fluoride, and conductive Ketjen black are fully ground, and an appropriate amount of NMP is added to form a uniform black paste slurry, which is applied to the current collector to form the positive electrode; the intermediate electrolyte is KL-Zn, which is assembled with the zinc negative electrode, positive electrode grams, negative electrode grams, gaskets, and battery shell shrapnel to form Zn / / NH4V4O 10 , Zn / / MnO2, Zn / / UPC@I button-type full battery).

[0046] Its material characterization and electrochemical performance are as follows:

[0047] Figure 1 The SEM, EDS and optical photographs of the solid electrolyte show that the prepared solid electrolyte has a stable surface morphology, and the EDS energy spectrum shows that the zinc ions are evenly distributed.

[0048] Figure 2 The Zn-Zn symmetric battery was tested at 0.2 mA cm -2 -0.1mA·cm -2 The comparison chart of long cycle stability performance shows that the zinc-zinc symmetrical battery made with the solid electrolyte prepared in Example 1 can be stably cycled for 2200 hours, which is better than the 140 hours of Comparative Example 1.

[0049] Figure 3 It can be seen from the scanning electron microscope that the surface of the zinc negative electrode after 10 cycles shows more uniform zinc deposition and less corrosion byproducts compared with comparative example 1.

[0050] Figure 4 NH4V4O is matched 10 Positive electrode, at 500mA·g -1 The discharge capacity can still be maintained at 259.2 mAh g after 200 cycles at the same current density. -1 The capacity retention rate is 83%, which shows a good capacity retention rate compared with Comparative Example 1 (46%).

[0051] Figure 5 NH4V4O is matched 10 The positive electrode was tested at different current densities. It can be seen from the figure that the full battery made with the solid electrolyte prepared in Example 1 has excellent rate performance. -1 It can still maintain 179.3mAh·g under high current discharge conditions. -1 When the current density is restored to 200 mA g -1 After that, the discharge capacity can reach 297.7 mAh g -1 .

[0052] Figure 6 The matched α-MnO2 cathode was tested at 500 mA g -1 The discharge capacity can still be maintained at 236.4 mAh g after 100 cycles at the same current density. -1 The capacity retention rate is 76.7%, which shows a good capacity retention rate compared with Comparative Example 1 (52.7%).

[0053] Figure 7 The matched UPC@I cathode was tested at 1000mA·g -1 The current density can be stably maintained for 160 cycles, which illustrates the universality of the solid electrolyte prepared in Example 1.

[0054] Example 2

[0055] The preparation method of the solid electrolyte of this embodiment can refer to Example 1, except that 0.10 g of solid electrolyte powder is weighed and tableted by a tablet press at a tableting pressure of 1000 Pa to obtain a solid electrolyte. The solid electrolyte is marked as KL-Zn-1.

[0056] The solid electrolyte prepared in this embodiment is assembled with the zinc negative electrode and the positive electrode sheet into a button-type zinc ion battery (the zinc sheet is cut into pieces as the negative electrode. NH4V4O 10 The active material, binder polyvinylidene fluoride, and conductive Ketjen black are fully ground, and an appropriate amount of NMP is added to form a uniform black paste slurry, which is applied to the current collector to form the positive electrode; and assembled into a button battery). -1 The discharge capacity can still be maintained at 225.5 mAh g after 200 cycles at the same current density. -1 .

[0057] Example 3

[0058] The preparation method of the solid electrolyte provided in this embodiment can refer to Example 1, except that 0.12 g of solid electrolyte powder is weighed and tableted by a tablet press at a tableting pressure of 1000 Pa to obtain a solid electrolyte. The solid electrolyte is marked as KL-Zn-2.

[0059] The solid electrolyte prepared in this embodiment is assembled with the zinc negative electrode and the positive electrode sheet into a button-type zinc ion battery (the zinc sheet is cut into pieces as the negative electrode. NH4V4O 10 The active material, binder polyvinylidene fluoride, and conductive Ketjen black are fully ground, and an appropriate amount of NMP is added to form a uniform black paste slurry, which is applied to the current collector to form the positive electrode; and assembled into a button battery). -1 The discharge capacity can still be maintained at 238.6 mAh g after 200 cycles at the same current density. -1 .

[0060] Example 4

[0061] The preparation method of the solid electrolyte of this embodiment can refer to Example 1, except that 0.18 g of solid electrolyte powder is weighed and tableted by a tablet press at a tablet pressure of 1000 Pa to obtain a solid electrolyte. The solid electrolyte is marked as KL-Zn-3.

[0062] The solid electrolyte prepared in this embodiment is assembled with the zinc negative electrode and the positive electrode sheet into a button-type zinc ion battery (the zinc sheet is cut into pieces as the negative electrode. NH4V4O 10 The active material, binder polyvinylidene fluoride, and conductive Ketjen black are fully ground, and an appropriate amount of NMP is added to form a uniform black paste slurry, which is applied to the current collector to form the positive electrode; and assembled into a button battery). -1 The discharge capacity can still be maintained at 240.2 mAh g after 200 cycles at the same current density. -1 .

[0063] Example 5

[0064] The preparation method of the solid electrolyte of this embodiment can refer to Example 1, except that 0.2 g of solid electrolyte powder is weighed and tableted by a tablet press at a tableting pressure of 1000 Pa to obtain a solid electrolyte. The solid electrolyte is marked as KL-Zn-4.

[0065] The solid electrolyte prepared in this embodiment is assembled with the zinc negative electrode and the positive electrode sheet into a button-type zinc ion battery (the zinc sheet is cut into pieces as the negative electrode. NH4V4O 10 The active material, binder polyvinylidene fluoride, and conductive Ketjen black are fully ground, and an appropriate amount of NMP is added to form a uniform black paste slurry, which is applied to the current collector to form the positive electrode; and assembled into a button battery). -1 The discharge capacity can still be maintained at 215.4 mAh g after 200 cycles at the current density -1 .

[0066] Comparative Example 1

[0067] Weigh 28.17g of zinc sulfate and place it in a beaker. Add 40mL of deionized water to the beaker and stir continuously for 30min under magnetic stirring to obtain a colorless, clear and transparent solution. Transfer the colorless, clear and transparent solution to a 50mL volumetric flask and continue to add deionized water to make up to volume to obtain an electrolyte. The electrolyte is labeled 2M-ZnSO4.

[0068] This embodiment is used to prepare a button-type zinc ion symmetrical battery composed of a solid electrolyte, a zinc sheet and a zinc sheet (the zinc sheet is cut into pieces, the positive and negative electrodes are both zinc sheets, the electrolyte is 2M-ZnSO4, and it is combined with a positive electrode, a negative electrode, a glass fiber diaphragm, a gasket, and a spring to form a symmetrical battery).

[0069] The 2M-ZnSO4 electrolyte prepared in this comparative example was used to assemble a button-type zinc ion battery with a zinc negative electrode and a positive electrode sheet (a zinc sheet was cut into pieces as a negative electrode, and NH4V4O 10, α-MnO2 active material, binder polyvinylidene fluoride, conductive Ketjen black are fully ground, an appropriate amount of NMP is added, and a uniform black paste slurry is formed, which is applied to the current collector to form a positive electrode; the positive electrode, zinc negative electrode, diaphragm, gasket, shrapnel, and battery shell are assembled into Zn / / NH4V4O 10 , Zn / / MnO2 button-type full battery). Matching NH4V4O 10 Positive electrode at 500mA·g -1 The discharge capacity can still be maintained at 146.7 mAh g after 200 cycles at the same current density. -1 , the retention rate is 46%. Matching α-MnO2 positive electrode at 500mA·g -1 The discharge capacity can still be maintained at 155.8 mAh g after 100 cycles at the same current density. -1 , the retention rate is 52.7%.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a solid electrolyte, characterized in that: The following steps are involved: The kaolin or sepiolite powder after centrifugal cleaning of impurities is mixed with the zinc salt electrolyte to perform ion exchange, and a solid electrolyte is obtained after centrifugal cleaning and drying; The specific steps include: (1) Wash kaolin or sepiolite powder with deionized water by centrifugation and dry to obtain impurity-free powder for later use; (2) mixing the impurity-free powder with a zinc salt electrolyte, stirring them fully to obtain a mixture, and centrifuging and washing the mixture, and drying it to obtain a solid electrolyte; Step (2) specifically includes the following process: The impurity-free powder and the zinc salt electrolyte are placed in a beaker, a stirring magnet is added, and the mixture is stirred at 400-600 r / min for 2-14 hours to obtain a mixture, and the mixture is then centrifuged and washed with deionized water, and dried to obtain a solid electrolyte; The zinc salt electrolyte is at least one of zinc sulfate electrolyte, zinc trifluoromethanesulfonate electrolyte, zinc chloride electrolyte, and zinc acetate electrolyte; the concentration of the zinc salt electrolyte is 1.5-3 mol / L; The usage ratio of the impurity-free powder and the zinc salt electrolyte is (1g-5g): (15mL-75mL); or the usage ratio of the impurity-free powder and the zinc salt electrolyte is (2g-4g): (25mL-50mL).

2. The method for preparing a solid electrolyte according to claim 1, characterized in that: The following steps are also included: (3) Weigh the solid electrolyte and use a tablet press to make a stable sheet-like solid electrolyte.

3. The method for preparing a solid electrolyte according to claim 2, characterized in that: The tableting pressure of the tablet press is 800-1200Pa.

4. The solid electrolyte prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the solid electrolyte according to claim 4 in the preparation of aqueous zinc ion batteries and aqueous zinc iodine batteries.

6. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises a battery housing and a positive electrode, a diaphragm and a negative electrode located in the battery housing, wherein the diaphragm is the solid electrolyte according to claim 4; or The positive electrode is at least one of a vanadium-based material, a manganese-based material and iodine-fixing high-activity carbon.

Citation Information

Patent Citations

  • Aqueous ion battery mixed-state electrolyte

    CN110994046A